The efficacy of quantitative fetal fibronectin in predicting spontaneous preterm birth in symptomatic women: A retrospective cohort study. (6th February 2019) - Nguyen, Anh Duy; Liu, Cathy Zhenao; Lehner, Christoph; Amoako, Akwasi Atakora; Sekar, Renuka
Abstract : Background: Recent data suggest that quantitative measurements of fetal fibronectin can be used accurately to predict increased risk of preterm birth. Aim: The purpose of this study was to demonstrate that the quantification of fetal fibronectin improves diagnostic accuracy in women who present with symptoms suggestive of threatened preterm labour (TPL) using a quantitative fetal fibronectin (qfFN) bedside analyser. Study design: This was a retrospective cohort study of pregnant women who presented between 22 +6 and 32 +6  weeks gestation with symptoms of TPL who had qfFN measured using the Rapid fFN Q10 system. The ability to predict spontaneous preterm birth (sPTB) within 48 h, 14 days and <34 weeks gestation at qfFN thresholds of 10, 50 and 200 ng/mL was assessed. Results: The overall rate of sPTB <34 weeks was 4.1% ( n  =   373). For deliveries within 48 h, within 14 days and <34 weeks, a qfFN threshold of 200 ng/mL had positive predictive values of 26.7%, 42.9% and 46.7%, respectively, when compared to patients with qfFN values of 0–9 ng/mL. The corresponding relative risks were 68.5, 53.8 and 38.0, respectively Conclusion: Quantitative fetal fibronectin testing with thresholds of 10, 50 and 200 ng/mL allows for more accurate prediction of preterm birth in symptomatic women. This higher degree of discrimination allows for more directed interventions for high‐risk patients and reduces the cost and burden of unnecessary treatment for low‐risk patients.